Eutectic Formation of Naproxen with Some Dicarboxylic Acids - Dahye Kim; Soeun Jang; Il Won Kim (MDPI AG, 2021)
Eutectic formation with additives is one of the established methods to improve the dissolution behaviors of active pharmaceutic ingredients (APIs). The improvement is mainly due to the increase in the surface area for dissolution, which originates from the finely divided micro-domains generated through the phase separation of the miscible liquid components upon solidification. The present study is to identify eutectic-forming additives for naproxen (NPX), a class II API of the biopharmaceutical classification system. A particular aim was to develop a eutectic mixture with NPX at least over 20 wt%, a minimum to be practical for oral delivery. Screening based on the proximity of the solubility parameter values identified dicarboxylic acids (succinic acid, glutaric acid, and suberic acid) as desirable additives for NPX. Binary melting diagrams were constructed to confirm the eutectic compositions, and the eutectic mixture with suberic acid (NPX 55 wt%) was further investigated. The dissolution (at pH 5.0) of the melt crystallized eutectics was enhanced compared to the simple physical mixture of the same compositions and neat NPX, which was attributed to the microscopically observed lamellar structures. The current study should support the systematic investigations of API eutectic mixtures by selecting appropriate eutectic-forming additives.